Improving the quality of Islamic schools through infrastructure services and school committee involvement - Sri Nurabdiah Pratiwi (Indonesian Journal Education, 2026)
This study investigates how facilities and infrastructure services and school committee involvement contribute to improving educational quality in Islamic schools. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected from 60 teachers and educational staff across three Islamic secondary schools using Likert-scale questionnaires and analyzed through descriptive statistics and multiple linear regression, while qualitative data were obtained from interviews, observations, and document analysis involving nine key informants. The results reveal that both variables simultaneously have a significant effect on school quality (R² ? 0.62–0.63; p less than 0.05), with facilities and infrastructure services showing a more dominant influence. Qualitative findings indicate that well-managed facilities enhance student motivation and teacher performance, whereas active school committees strengthen governance through planning, supervision, and community engagement. The integration of findings demonstrates that synergy between effective facilities management and participatory governance creates a sustainable ecosystem for improving academic achievement, character development, and stakeholder satisfaction in Islamic schools.